Islamic Financial Literacy and Household Financial Behavior in the Digital Era: A Conceptual Synthesis of Contemporary Literature - Erizal Candra Efendi; Robi Harjoni Putra; Ruri Mustika; Wildan Hadi; Hafni Juniyanti Hsb (Al-bank: Journal of Islamic Banking and Finance, 2026)
This study aims to synthesize contemporary literature on Islamic financial literacy and its relationship with household financial behavior in the digital era. Employing a qualitative library research design, this study systematically reviews peer-reviewed journal articles, academic books, and institutional reports published over the last decade. Data were collected through structured searches of major academic databases and analyzed using qualitative content analysis, including thematic coding, categorization, and comparative synthesis. The findings indicate that Islamic financial literacy is a multidimensional construct encompassing cognitive understanding of Sharia-based financial principles, financial management skills, and ethical orientations. Higher literacy levels are associated with more structured household financial practices, such as disciplined budgeting, saving orientation, and cautious engagement with digital Islamic financial services. Furthermore, digital financial environments significantly influence household financial decision-making and access to information. This study proposes an integrative conceptual framework linking Islamic financial literacy dimensions with household financial behavior through cognitive, ethical, and behavioral mechanisms. The findings contribute to clarifying the role of Islamic financial literacy in digital financial contexts and provide theoretical insights for future empirical research. Practically, this study offers policy-relevant implications for designing effective financial literacy initiatives aimed at enhancing financial resilience and sustainable financial practices among Muslim households in the digital era